Organizational perspective on women senior-managers in Kazakhstan:Examination of leadership roles, updating evidence and research agenda - Tankibayeva А.; McDonald, S. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2019)
The article aims to update the evidence and to diversify the research agenda on leadership roles of women senior-managers. This research work draws attention to the essential gap in the research of women as senior-managers and organizational leaders. In the first place, it notices that while the conceptualization of leadership has expanded to define leadership from interpersonal to organizational influence, the research on women leadership has not updated accordingly. The article claims that research agenda on women in organizations overlooks examination of women as senior-managers and respectively overlooks understanding of the leadership roles that women perform to organizations. Second, the article aims to examine and update the evidence as per the interplay of gender and women senior-managers’ leadership roles in organizational context. Namely, the research examines how women senior-managers perceive their leadership mandate, and whether organizations enable or constrain it. Results of the 21 indepth semi-standardized interviews identified three distinct leadership roles that women senior-managers perceive as requisite for the roles of senior-manager. That is followed by a discussion of implications for organizational leadership theory and organizational routines. Key words: women senior-managers, gender, organizational behavior, leadership roles.